Diethyl Malonate-Based Turn-On Chemical Probe for Detecting Hydrazine and Its Bio-Imaging and Environmental Applications With Large Stokes Shift - Qu, Jianbo; Zhang, Zhi-Hao; Zhang, Haitao; Weng, Zhen-Tao; Wang, Jian-Yong (Frontiers in Chemistry, 2021)
Diethyl malonate based fluorescent probe NE-N2H4 was constructed for monitoring hydrazine (N2H4). The novel probe NE-N2H4 exhibits good properties, such as large Stokes shift (about 125 nm), good selectivity and low cytotoxicity. This turn-on probe NE-N2H4 can be operated to detect hydrazine in the living HeLa cells. Especially, after soaking in probe solution, the TLC plate could detect the vapor of hydrazine. Therefore, the probe NE-N2H4 could be used to monitor hydrazine in biosamples and environmental problem.